The Role of Second-Person Information in the Development of Social Understanding - Chris Moore; John Barresi (Frontiers in Psychology, 2017)
We consider the second-person or interactive approach to social understanding, conceived as an understanding of intentional relations. We identify five forms of second-person information – self-directedness, contingency, reciprocity, affective engagement, and shared intentions – that occur only in interactions. We assess the extent to which these forms of information are available to observers of interactions as well as to the participants of an interaction and conclude that whereas observers may gain some second-person information, interactive participants have a privileged position. We also ask whether these forms of second-person information can deliver social understanding in terms of the understanding of intentional relations that are descriptive of persons. We argue that whereas none of these forms alone is sufficient for understanding intentional relations, they all play an important role in the developmental processes that enable the construction of social understanding. Therefore, the second-person approach, understood as theorizing how second-person information available in interactions is used in the development of social understanding, is a critically important approach to a full theory of social understanding.